Reimagining authorship guidelines to promote equity in co-produced academic collaborations. Issue 10 (3rd October 2022) - Miles, Sam; Renedo, Alicia; Marston, Cicely
ABSTRACT: Authorship of academic papers is a currency that can bring career advantages in academia and other industries. How authorship should be decided is not always clear, particularly in co-produced research with non-academic collaborators, for which existing authorship guidelines are largely silent. In this paper, we critically reflect on what constitutes written authorship in the context of co-produced health research. We present examples from our own work to illustrate the argument we make, including publishing a co-authored paper with non-academic partners. We consider questions of what constitutes authorship and how it is mutually understood. We discuss some of the opportunities and limits to participation and how these might translate into academic authorship as a collaborative research output. Finally, we explore the potential of authorship guidelines as a resource for critical reflection on what we mean by co-produced work and how we recognise contributions to global health research. We suggest that authorship guidelines should be adapted to encourage attribution of co-produced research to include non-academic as well as academic collaborators, and we provide a draft guideline for how this might be done.